(untitled) (Journal on studies and research of academic knowledge, 2015)
Metformin, a biguanide belonging to category B in pregnancy according to the classification of drugs by the FDA (Food and Drugs Administration), is used as a new treatment option in the management of patients with gestational diabetes. The following open experimental research, with probability sampling, discusses the effectiveness of this drug in patients interned in the room of high risk for Mothers and Children in the Hospital Queen. Sofia of the Paraguayan Red Cross during September 1, 2012 to September 1, 2013. Statistically significant results in patients treated with metformin were achieved.